(untitled) (Research, Society and Development, 2025)
Moyamoya disease is considered rare and its origin is still unknown, but there is a genetic condition associated with the RNF213 gene related to the disease. However, Asian ethnicity, especially Japanese, is more affected by the disease. The objective of this review was to analyze Moyamoya disease, comorbidities associated with the disease, diagnostic methods, treatments and challenges faced by those with the disease. An integrative review of scientific articles consulted from databases such as the Virtual Health Library (VHL) - BIREME - PAHO - WHO and Medical Publications (PubMed) - via the National Library of Medicine (NLM) and some websites related to the disease in the last 23 years was used as methodology. After consulting the databases, 18 articles were selected, 6 about the disease, associated comorbidities and diagnosis, 6 about treatments, 3 about factors that influence treatment and 3 about life expectancy and quality of life, many of which are case reports. Referring to a rare and serious disease, there is a need for further studies related to MMD, since this disease is often associated with other rare and serious comorbidities, and requires surgical and multidisciplinary treatment for the patient to have a better quality of life and life expectancy. There is much to be explored regarding MMD to improve quality of life, considering that it is an incurable disease to this day with very limited treatment alternatives.